2014
DOI: 10.1101/gr.180893.114
|View full text |Cite
|
Sign up to set email alerts
|

Single haplotype assembly of the human genome from a hydatidiform mole

Abstract: A complete reference assembly is essential for accurately interpreting individual genomes and associating variation with phenotypes. While the current human reference genome sequence is of very high quality, gaps and misassemblies remain due to biological and technical complexities. Large repetitive sequences and complex allelic diversity are the two main drivers of assembly error. Although increasing the length of sequence reads and library fragments can improve assembly, even the longest available reads do n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 47 publications
1
83
0
1
Order By: Relevance
“…CH17 clone placements were performed and evaluated as described in Schneider et al (2013) and Steinberg et al (2014). On the GCA_001307025.1 assembly, the average insert length was 208,547 and the standard deviation was 19,641.…”
Section: Wgs Mini-contig Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…CH17 clone placements were performed and evaluated as described in Schneider et al (2013) and Steinberg et al (2014). On the GCA_001307025.1 assembly, the average insert length was 208,547 and the standard deviation was 19,641.…”
Section: Wgs Mini-contig Generationmentioning
confidence: 99%
“…Although we were able to improve or resolve some path problems through reordering of existing assembly components to match optical maps, we found that other approaches were needed at more complex regions where allelic and paralogous variation made it impossible to confidently define paths with clones representing a mosaic of diploid DNA sources. In these instances, we replaced GRCh37 components with new tiling paths comprised of BAC clones representing the single haplotype of the essentially haploid CHM1 genome (Dennis et al 2012;Steinberg et al 2014), or on Chromosome X, with the single haplotype represented in RP11 (Mueller et al 2013). We also retiled several genomic loci associated with immune responses (IGK, IGH, LRC-KIR, and the cytokine cluster on 17q) with CHM1 clones, replacing the unvalidated mosaic representations in GRCh37 and previous assembly versions to ensure the reference-provided representations of these clinically important regions that actually exist Watson et al 2013Watson et al , 2015.…”
Section: Retilingmentioning
confidence: 99%
See 1 more Smart Citation
“…These advances have allowed researchers to perform clade genomics, producing assemblies for multiple members of a species or clade [130,131], and are required for the ambitious goals of projects such as Genome 10K [42] which aim to produce thousands of assemblies of diverse organisms. In addition, efforts are growing to produce de-novo assemblies of individual humans to evaluate the human health implications of structural variation and variation within regions not currently accessible with reference assisted approaches [132,133,134].…”
Section: Introductionmentioning
confidence: 99%
“…The nearly ubiquitously used alignment program Burrows-Wheeler Aligner (BWA) has detailed capabilities for dealing with these alternate loci (68). A new alternate loci-tolerant aligner (SRPRISM) and companion reference-guided assembly tool (ARGO) have recently been described as part of a study to assemble a single-haplotype genome derived from a hydatidiform mole (112). The assembly of the haploid DNA from the hydatidiform mole has added to the curation framework available for genome annotation and assembly and provided at least one accurate allelic representation across loci with a complex genomic architecture.…”
Section: Toward a Reference-free Analysismentioning
confidence: 99%